2015
DOI: 10.1109/tsg.2015.2397887
|View full text |Cite
|
Sign up to set email alerts
|

A Monitoring Technique for Reversed Power Flow Detection With High PV Penetration Level

Abstract: Abstract-Theintegration of renewable energy resources (RESs) in power systems poses many research challenges. Research shows that the RES output may exceed the consumed power during the day. Consequently, the direction of the power flow on distribution lines can be reversed during some periods. As the voltage regulator is normally designed for unidirectional power flow, this may cause voltage violations on the distribution feeder. Therefore, most utilities try to set a penetration level (PL) limit for safe ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 35 publications
(45 reference statements)
1
52
0
1
Order By: Relevance
“…The capability of the impedance based method for reverse power flow detection was shown in [15]. In this paper it will be shown that the apparent impedance has a good potential for monitoring of feeder power factor, in addition to reverse and forward active and reactive power flow.…”
Section: Measured Impedance Trajectory and Power Flowmentioning
confidence: 93%
See 2 more Smart Citations
“…The capability of the impedance based method for reverse power flow detection was shown in [15]. In this paper it will be shown that the apparent impedance has a good potential for monitoring of feeder power factor, in addition to reverse and forward active and reactive power flow.…”
Section: Measured Impedance Trajectory and Power Flowmentioning
confidence: 93%
“…To do so, for an impedance measuring unit , located at sending end of Fig.1 (bus 1) the apparent impedance measured by an impedance measuring unit is calculated by [15]:…”
Section: B Mapping Between P-q and Z Planementioning
confidence: 99%
See 1 more Smart Citation
“…Multilevel inverters are designed based on configuration of more switches and DC supplies to achieve the goal of generating various voltage levels at the output. Such inverters generate low harmonic waveforms; therefore they are most suitable for energy conversion applications to deliver efficient power to the loads from renewable energy sources like photovoltaic systems [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the selectivity and speed should be in an acceptable level. Communication assisted protection strategies are a common solution to protect the microgrid [5][6][7][8][9]. Common issues like sympathetic tripping, false tripping, blind zone, variation in fault levels and unwanted islanding are caused due to the impact of distributed generations [10].…”
Section: Introductionmentioning
confidence: 99%